Understanding catalytic mechanisms of HZSM-5 in hydrothermal liquefaction of algae through model components: Glucose and glutamic acid. (November 2019) - Yang, Wenchao; Wang, Zhaowei; Song, Shuang; Chen, Hong; Wang, Xiaomeng; Cheng, Jiayi; Sun, Ruijun; Han, Jianbo
Abstract: Hydrothermal liquefaction (HTL) of algae has attracted great interest as a thermal conversion for biofuels. In an effort to understand the catalytic mechanism by which algae undergoes HTL in the presence of HZSM-5, the different roles of the major components (carbohydrates and proteins) were investigated. Glucose and glutamic acid were selected as model compounds of carbohydrates and proteins, respectively. Glucose, glutamic acid, and their binary mixtures were processed under hydrothermal conditions in the presence of HZSM-5 over a temperature range of 220–330 °C. The products were analyzed using a combination of elemental analysis (EA), thermal gravimetric analysis (TGA), gas chromatography mass spectrometry (GC-MS), and Fourier transform infrared (FT-IR) spectroscopy to characterize the physicochemical properties. The effects of HZSM-5 on the yield and quality of bio-oil were investigated. Results indicated that the addition of HZSM-5 did not significantly affect the bio-oil yield of glutamic acid but increased the bio-oil yields from glucose and their binary mixtures. The hydrogen-to-carbon (H/C) ratio and the higher heating values (HHVs) of the bio-oils were all greatly increased in the presence of HZSM-5. The addition of HZSM-5 reduced the contents of undesirable oxygenated compounds, nitrogenous compounds, and increased the hydrocarbon content. Maillard reactions between glucose and glutamic acid were also strengthened by HZSM-5. Highlights: HTL of glucose, glutamic acid and the binary mixtures with HZSM-5 were studied. HZSM-5 improved bio-oil formation from HTL of glucose or binary mixtures. H/C ratio and HHVs of the bio-oils increased greatly in the presence of HZSM-5. Deep degradation of the liquefied intermediates was promoted by HZSM-5.